High level, context dependent misincorporation of lysine for arginine in Saccharomyces cerevisiae a1 homeodomain expressed in Escherichia coli. - Forman, M. D. (Cold Spring Harbor Laboratory Press, 1998)
The Saccharomyces cerevisiae a1 homeodomain is expressed as a soluble protein in Escherichia coli when cultured in minimal medium. Nuclear magnetic resonance (NMR) spectra of previously prepared a1 homeodomain samples contained a subset of doubled and broadened resonances. Mass spectroscopic and NMR analysis demonstrates that the heterogeneity is largely due to a lysine misincorporation at the arginine (Arg) 115 site. Arg 115 is coded by the 5'-AGA-3' sequence, which is quite rare in E. coli genes. Lower level mistranslation at three other rare arginine codons also occurs. The percentage of lysine for arginine misincorporation in a1 homeodomain production is dependent on media composition. The dnaY gene, which encodes the rare 5'-AGA-3' tRNA(ARG), was co-expressed in E. coli with the a1-encoding plasmid to produce a homogeneous recombinant a1 homeodomain. Co-expression of the dnaY gene completely blocks mistranslation of arginine to lysine during a1 overexpression in minimal media, and homogeneous protein is produced.